Spirituality in the Philosophical Thought of Seyyed Hossein Nasr - Fadhilah Khunaeni (Universitas Islam Negeri Mataram, 2016)
Spirituality for Seyyed Hossen Nasr is an inner reality that becomes a religious central in Islam. It is the esoteric dimension hidden in the reality of exoteric Islam. That view on spirituality brings Nasr to the philosophical thought that cannot be separated from religious metaphysical doctrine. Nasr argues that philosophy is more than just a ratio but also the activity of intellect that can reach the meta-cosmic nature to find the essence of truth namely the universal and eternal truth that lies behind the physical and relative truth. The philosophical efforts to find this truth are a combination of the optimizing potential of reason and intellectual intuition. Nasr refers to ḥikmah or wisdom as a kind of philosophy that combines logic and intellectual intuition. That philosophical view brings Nasr on a dualistic view of nature which not only has a cosmic dimension as such but also has a meta-cosmic dimension. This dualistic view is his fundamental reason in formulating the concept of metaphysical cosmology as a solution to the crisis of modern science that has caused a variety of ecological damage due to the secular vision. DOI: http://dx.doi.org/10.20414/ujis.v20i2.812